Synthesis of Pt/mesoporous SiC-15 and its catalytic performance for sulfuric acid decomposition - Khan, Hassnain Abbas; Natarajan, Prakash; Jung, Kwang-Deog (ELSEVIER SCIENCE BV, 2018)
Sulfuric acid (SA) decomposition is one of the key reactions in the sulfur-iodine (SI) cycle to produce hydrogen. Catalysts for the SA decomposition should be active and stable in a wide temperature range of 550-850 degrees C to absorb latent heat generated from a thermal solar heat or a very high temperature nuclear reactor. Here, mesoporous mSiC-15 is prepared using the SBA-15 template. TEM analysis shows that the morphology of the mSiC-15 has the replica structure of SBA-15. Pt/SBA-15 and Pt/mSiC-15 catalysts are prepared by impregnation and the catalytic activity is examined under the reaction condition of 650-850 degrees C and a GHSV of 76,000 mL/g(cat)/h. The Pt/mSiC-15 catalyst is relatively stable for 50 h at 850 degrees C, while the Pt/SBA-15 was severely deactivated. The Pt amounts on the Pt/SBA-15 and Pt/mSiC-15 catalysts decreased from 0.73 and 0.80 wt% at initial reaction time to 0.39 and 0.68 wt% after 12 h reaction, respectively. The Pt loss during the SA reaction is main cause of deactivation, which is caused by the evaporation of Pt oxides under O-2 environment produced during the SA decomposition. It is observed that the Pt particles are embedded in porous SiO2 (Pt/mSiO(2)), which is transformed from Pt/mSiC-15 during the SA decomposition for 6 h. The Pt/mSiC-15 was relatively active and stable for the SA decomposition and the Pt loss was minimized by the structural change from Pt/mSiC-15 to Pt/mSiO(2) after 6 h.
Keywords: CYCLE HYDROGEN-PRODUCTION; METAL-OXIDE CATALYSTS; THERMAL-STABILITY; MESOPOROUS SILICA; SI CYCLE; PLATINUM NANOPARTICLES; PRODUCE HYDROGEN; SBA-15; DESORPTION; BEHAVIOR